Transfusion Strategies in Patients with Mitral Valve Replacement - Gumeniuk, B. M.; Golota, I. P. (Ukrainian Journal of Cardiovascular Surgery, 2021)
The aim. To carry out research of liberal, restrictive and blood-saving transfusion strategies in patients with mitral valve replacement (MVR) in the conditions of artificial blood circulation during operation, in intensive care unit, and in the postoperative period. Material and methods. Retrograde examinations were performed in 70 patients who underwent surgery for ac-quired mitral valve disease. Our research consisted of three stages: stage 1 involved the study of the volume of transfu-sions of donor blood components during MVR, stage 2 involved the study of the volume of transfusion of donor blood components in the emergency room, stage 3 involved the study of the volume of transfusions of donor blood components in the intensive care unit. All the patients were divided into 3 groups. Group A included 14 patients in whom (arbitrary) liberal transfusion strategy (LTS) with transfusion of donor blood components was applied during the operation. Group B included 19 patients in whom (economical) restrictive transfusion strategy (RTS) during surgery with transfusion of donor blood components was applied. Group C included 37 patients in whom the patient’s autologous blood-saving tech-nology (BST) was applied during the operation. Results and discussion. At stage 1 of the study, the volume of packed RBCs per 1 transfusion in group A exceeded the volume of packed RBCs per 1 transfusion in group B by 68.0%. The volume of transfusions of native fresh-frozen plasma (FFP) in group A exceeded that in group B by 73.5%. The volume of platelet transfusions (PT) in group A at stage 1 was 75.0%. At stage 2 of the study, the total volume of PT in patients of group A was still 3.0 times higher and FFP was 2.7 times higher than that in group B. At this stage of the study, there was also a 2.6-fold decrease in the volume of PT per 1 transfusion in group B compared with group A. In total, during 3 stages of the study, the volume of PT use in group A was 5.7 times higher, and in group B it was 3.9 times higher than that in group C. The volume of FFP use in group A was 4.4 times higher, and in group B it was 3.8 times higher than that in group C. Conclusions. The use of LTS in group A and RTS in group B resulted in 5.2-fold and 3.8-fold increase in the total volume of transfused donor blood components, repsectively, compared to group C.